Candida spp. prevalence in well controlled type 2 diabetic patients with denture stomatitis - Sanita, Paula Volpato; Pavarina, Ana Claudia [UNESP]; Giampaolo, Eunice Teresinha; Silva, Mariana Montenegro; de Oliveira Mima, Ewerton Garcia; Ribeiro, Daniela Garcia; Vergani, Carlos Eduardo [UNESP] (Mosby-elsevier, 2011)
Objective. The aim of this study was to compare the prevalence of Candida spp. in diabetics and nondiabetics with and without denture stomatitis (DS).Study design. Mycologic samples were taken from the dentures of 90 healthy subjects (control group [CG]), 80 denture stomatitis nondiabetics (DSND), and 40 denture stomatitis diabetics (DSD; well controlled type 2) for identification of Candida spp. Results were analyzed by Fisher exact test, Bonferroni-corrected confidence interval, and chi(2) test (alpha = .05).Results. Candida albicans was the predominant species isolated (81.9%; P < .016), with C. tropicalis and C. glabrata demonstrating similar prevalence (15.71% and 15.24%, respectively). The prevalence of C. albicans and C. tropicalis in the DS groups were significantly higher (P < .01) than in the CG. The prevalence of C. tropicalis significantly increased with the highest degree of inflammation (P < .05).Conclusions. The prevalence of Candida spp. was similar between diabetic and nondiabetic patients with DS. Candida tropicalis may play a role in the progression of DS. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2011; 111: 726-733)